Aspectos ecológicos associados à duas diferentes espécies de macrófitas submersas enraizadas. - Meurer, Thamis (2015)
Rooted submersed macrophytes play different roles in aquatic ecosystems and their dynamics are influenced by different biotic and abiotic factors. Ecological aspects associated to the species Egeria najas Planch. and Hydrilla verticillata (Lf) Royle (Hydrocharitaceae) are reported. Using data obtained during one year of sampling in a lake, the species E. najas was studied on the theory of alternative stable states. Coexistence of alternative states was detected and the factors involved in simultaneous occurrence of alternative states was discussed. The results indicate that the turbid water state and absence of macrophytes and the clear water state dominated with E. najas are maintained by multiple factors, mainly the radiation and the local effect of macrophytes. After, the species E. najas and H. verticillata were studied with the hypothesis of biotic resistance through a series of experiments. The effects of biotic interactions between macrophytes and the snails Pomacea canaliculata (Lamarck, 1822), a macrophyte consumer and Physa acuta (Draparnaud, 1805), an epiphyton consumer, and the effects of these interactions with the failure of the establishment of exotic invasive H. verticillata in ponds associated with the Paraná River were discussed. The results of the experiments indicated that P. canaliculata indicated a feeding preference for H. verticillata and may confer biotic resistance to the invaded environment through the consumption of the macrophytes biomass and that P. acuta increases its activity according to the availability of food, but did not affected the performance of the macrophytes under the experimental conditions established.